'I feel like my house was taken away from me': Parents’ Experiences of Having Home Adaptations for Their Medically Complex, Technology-Dependent Child - Mitchell, Tracy Karen; Bray, Lucy; Blake, Lucy; Dickinson, Annette; Carter, Bernie (Wiley, 2022)
Technology-dependent children are a sub-population of seriously ill children with life-limiting conditions who are being cared for at home by their families. Although home-based care has been the model of care for these children since the late 1980s, there is a paucity of literature about parents' experiences of having home adaptations made to enable their home to be a place of care for their child. Using the findings from auto-driven photo-elicitation interviews conducted between August 2017 and June 2018 with 12 parents (10 mothers and 2 fathers) who have a technology-dependent child (aged 5-25 years) living in England, Scotland and Wales and David Seamon's five concepts of at-homeness (appropriation, at-easeness, regeneration, rootedness and warmth) as a conceptual framework, this paper addresses how parents' experienced home adaptations. Thematic analysis generated a meta-theme of 'Home needs to be a home for all family members' and the three key themes: (1) 'You just get told' and 'you're not involved'; (2) It's just the 'cheapest', 'quickest', 'short-term' approach; (3) Having 'control' and 'thinking things through.' The need to involve parents in decision-making about adaptations that are made to their home (family-informed design) is clear, not only from a cost-saving perspective for the state, but for creating an aesthetic and functional home that optimises health, well-being and feelings of at-homeness for the entire family.
Keywords: biotechnology; families with disabled and/or chronically Ill children/young people; home adaptations; home care; medical home; patient-centred care; 4203 Health Services and Systems; 42 Health Sciences; 44 Human Society; Pediatric; Behavioral and Social Science; 7 Management of diseases and conditions; 7.1 Individual care needs; Generic health relevance; 3 Good Health and Well Being; 1117 Public Health and Health Services; 1607 Social Work; Nursing; 4206 Public health; 4409 Social work; Humans; Palliative Care; Parents; Mothers; Technology; Child; Home Care Services; Female; Female; Child; Humans; Parents; Home Care Services; Palliative Care; Mothers